Proceedings of the 8th Workshop on Asian Translation (WAT2021) 2021
DOI: 10.18653/v1/2021.wat-1.17
|View full text |Cite
|
Sign up to set email alerts
|

Improved English to Hindi Multimodal Neural Machine Translation

Abstract: Machine translation performs automatic translation from one natural language to another. Neural machine translation attains a state-ofthe-art approach in machine translation, but it requires adequate training data, which is a severe problem for low-resource language pairs translation. The concept of multimodal is introduced in neural machine translation (NMT) by merging textual features with visual features to improve low-resource pair translation. WAT2021 (Workshop on Asian Translation 2021) organizes a share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…is score was later improved again in the WAT2020 [12] task, where a BLEU score of 33.57 was obtained on the challenge test set. In [7], a bidirectional RNN of encoder type (BRNN) and a double-attention RNN of decoder type with default settings are used, and pretrained words are used to embed the data of monolingual corpus and additional parallel corpus IITB. In the WAT2021 multimodal translation task, [13] attempted to employ phrase pairs to improve English to Hindi translation effectiveness and performance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…is score was later improved again in the WAT2020 [12] task, where a BLEU score of 33.57 was obtained on the challenge test set. In [7], a bidirectional RNN of encoder type (BRNN) and a double-attention RNN of decoder type with default settings are used, and pretrained words are used to embed the data of monolingual corpus and additional parallel corpus IITB. In the WAT2021 multimodal translation task, [13] attempted to employ phrase pairs to improve English to Hindi translation effectiveness and performance.…”
Section: Related Workmentioning
confidence: 99%
“…In our experiments, we extract image features by different models and then add image features information to the encoder side of the baseline, fuse it with the initial word encoding information and position embedding information, and train an encoder containing image features, followed by a standard decoder module at the same time, to form a complete encoder and decoder model, thus improving the quality of English to Hindi translation. Comparing the experimental results, our approach improves 3 BLEU on the test set compared to the [7] method, and we also use different models to extract the image feature information and compare the impact of the extracted features on the translation results under different models.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it was observed that using multimodal methods achieves better results [42,61] compared to UNMT or image captioning. Doubly Attentive decoder [8] architecture, which was proven to generate a better translation for other languages, was adopted for English-Hindi [37,38]. They use pre-trained word embedding learned from IITB Corpus [34] to initialize the models and augment datasets by using Giza++ Tool [48], to obtain phrase pairs.…”
Section: Multimodal Translation On Indian Languagesmentioning
confidence: 99%
“…High-quality translation involves a detailed concern of the source text and it enables effective and excellent language skills. Neural machine translation (NMT) is a new machine translation methodology [3]- [5] that helps to gain significantly in the evaluation of humans compared to statistical machine translation (SMT) systems. It's a whole end-to-end system designing one (or more) layers of machine translation into one huge neural network.…”
Section: Introductionmentioning
confidence: 99%